Expression of aquaporin 1, 5 and 9 in the ovarian follicles of cycling and early pregnant pigs - Skowronska, A; Mlotkowska, P; Eliszewski, M; Nielsen, S; Skowronski, M T (Physiological research, 2015)
Aquaporins (AQPs) are water channel proteins responsible for water homeostasis and important for proper functioning of all body systems, including reproductive structures. This study was designed to determine their localization and quantitative changes in the pig ovary during different stages of the estrous cycle and early pregnancy. The expression of AQP 1, 5 and 9 proteins was determined by immunocytochemistry and Western blot analyses. AQP1 was found in the plasma membranes of capillary endothelium, AQP5 - in the plasma membranes of granulosa cells of developing follicles and flattened follicle cells of the primordial follicles, and AQP9 - in granulosa cells of the developing follicles. In the cyclic pigs, the expression of AQP1 and 5 proteins was the highest on Days 18-20, but did not change significantly between Days 2-4, 10-12 and 14-16 of the cycle. In pregnant pigs (Days 14-16 and 30-32), the expression of AQP1 and 5 did not change and was similar to that observed during Days 10-12 and 14-16. In turn, AQP9 expression did not change between all studied periods. In conclusion, studied AQP are localized in different cells populations, the endothelial and granulosa cells, and AQP1 and 5 seem to be crucial for follicular development in pigs.
Keywords: Granulosa Cells; buněčná membrána; Pregnancy; Endothelium, Vascular; cévní endotel; akvaporin 1; Female; zvířata; Immunohistochemistry; akvaporiny; Aquaporin 1; imunohistochemie; Swine; Estrous Cycle; folikulární buňky; Aquaporin 5; ženské pohlaví; Aquaporins; těhotenství; ovariální folikul; ovarium; estrální cyklus; Ovarian Follicle; akvaporin 5; Animals; Cell Membrane; Ovary; prasata